An assessment of the food safety knowledge and attitudes of food handlers in hospitals - Lesiba A. Teffo; Frederick T. Tabit (BMC, 2020)
Abstract Background The possession of inadequate food safety knowledge (FSK) by food handlers poses a serious threat to food safety in service establishments. The aim of this research was to investigate factors that influenced the FSK and food safety attitudes (FSA) of employees involved in the preparation and/or the serving of food from nine hospitals in the Capricorn District Municipality (CDM) in Limpopo Province, South Africa. Method Up to 210 individuals (18-65 years) who were employed in these hospitals, and who were involved in the preparation and serving of food to patients were purposefully selected. Data collection was by means of an interview using a questionnaire design for this study. The FSK and FSA scores of hospital food handlers were obtained by adding the correct response to FSK or FSA questions. Results Only 29% of the hospital food handlers have attended a food safety-training course. Many food handlers were not knowledgeable on the correct temperature for handling foods, and on the correct minimum internal cooking temperature for poultry, seafood and egg. Only the minority of food handlers knew that Salmonella is the main foodborne bacteria pathogen mostly associated with poultry products (47.1%) and that food borne bacteria will grow quickly in food at a temperature of 37 °C (38.1%). Hospital food handlers with higher academic qualifications do not possess more FSK than those with lower academic qualifications. 51% of the hospital food handlers possessed a Satisfactory FSK while 10% possessed a Good FSK and 39% possessed an Inadequate FSK. Conclusion More than 60% of the hospital food handlers possesses either Good FSK or Satisfactory FSK. Higher levels of education, experience in food handling and job position did not lead to better FSK outcome. All the hospital food handlers possess at least a Satisfactory FSA. There was a weak positive but significant correlation between the FSK and FSA of hospital food handlers. It is recommended all employees involved in food handlers be subjected to food safety training programmes on a regular basis irrespective of their academic, employment and training details.